Viral threat in the dentist’s work - Polz, Dorota; Polz-Dacewicz, Małgorzata; Pedrycz-Wieczorska, Agnieszka (Polish Journal of Public Health, 2012)
Dentists are a professional group that is extremely exposed to viral infections. It results from the specificity of their work; dentists operate with sharp and rotary tools, work in respiratory paths in direct contact with patients and water-air spray is created during many operations. In dentistry, pathologic microorganisms can be spread in a number of ways. While analyzing viral threat to dental crew, hospital infections must be taken into consideration. Dental operating rooms may be a potential place where viral infection can spread from patients to personnel, from personnel to patients or between patients. The issue in question is extremely up-to-date and the number of lawsuits on account of infections and amounts of damages is on the rise. The proportion of claims about dental operating rooms makes 6.3% of the total of claims in Poland. Basing on the above assumptions, the constant education of dental staff about the prevention of viral infections and the rise of the awareness about of the issue are needed. There arenumerous viruses that can pose a threat to dental staff. Some of them are frequently described and certainly well-known; in this article, some of them will be described; those which are relevant to the number of illnesses and the weight of consequences, and those which are perhaps less often, in dentists mind-sets, connected to dental procedures. In this article we analyzed the role of hepatitis B and C viruses, some of herpes viruses, influenza virus, HPV, TTV and BK virus.